Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Consider the following linear recurrence sequence.

$x_1 = 11$, $x_{n+1} = -0.8x_n + 9,\quad n = 1,2,3, \ldots.$

Find a closed form for this sequence.

share|improve this question
    
What did you try? –  Davide Giraudo Feb 1 '12 at 18:59
2  
en.wikipedia.org/wiki/… –  yoyo Feb 1 '12 at 19:05
    
You should really try to write out the first few terms and see what happens if you have nowhere to go. –  Patrick Da Silva Feb 1 '12 at 19:08
add comment

3 Answers

To get an idea of what the closed form might look like, let's iterate the relation a few times: $$ \begin{align} x_n &=9-.8x_{n-1}\\ &=9-.8(9-.8x_{n-2})\\ &=9-.8\cdot9+.8^2x_{n-2}\\ &=9-.8\cdot9+.8^2(9-.8x_{n-3})\\ &=9-.8\cdot9+.8^2\cdot9-.8^3x_{n-3}\tag{1} \end{align} $$ Looking at $(1)$, it appears that $$ x_n=9\frac{1-(-.8)^k}{1+.8}+(-.8)^kx_{n-k}\tag{2} $$ Equation $(2)$ can be verified using induction.


Verification: The case $k=1$ is just the given recursion: $x_n=9-.8x_{n-1}$.

Suppose $(2)$ is true for some $k$, then $$ \begin{align} x_n &=9\frac{1-(-.8)^k}{1+.8}+(-.8)^kx_{n-k}\\ &=9\frac{1-(-.8)^k}{1+.8}+(-.8)^k(9-.8x_{n-k-1})\\ &=9\frac{1-(-.8)^k}{1+.8}+9(-.8)^k+(-.8)^{k+1}x_{n-k-1}\\ &=9\frac{1-(-.8)^{k+1}}{1+.8}+(-.8)^{k+1}x_{n-k-1}\\ \end{align} $$ So $(2)$ is true for $k+1$.


Using $x_1=11$ and $k=n-1$, $(2)$ becomes $$ \begin{align} x_n &=5(1-(-.8)^{n-1})+(-.8)^{n-1}11\\ &=5+6(-.8)^{n-1}\tag{3} \end{align} $$

share|improve this answer
add comment

$x_{n+1}+a=-0.8(x_n+a)$

if a=-5, this equation is equivalent to $x_{n+1}=-0.8x_n+9$

then we obtain:

$x_n-5=(-0.8)^{n-1}(x_1-5)$

Thus:

$x_n=5+6(-0.8)^{n-1}$

share|improve this answer
add comment

Use generating functions. Define $X(z) = \sum_{n \ge 0} x_{n + 1} z^n$, multiply the recurrence by $z^n$ and sum over $n \ge 0$ to get: $$ \frac{X(z) - x_1}{z} = - \frac{4 X(z)}{5} + \frac{9}{1 - z} $$ Thus: $$ X(z) = \frac{55 - 10 z}{5 - z - 4 z^2} = 5 \cdot \frac{1}{1 - z} + 6 \cdot \frac{1}{1 + 4 z / 5} $$ Two geometric series: $$ x_{n + 1} = 5 + 6 \cdot (-0.8)^n $$

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.